Palliative Treatment In Nasopharyngeal Carcinoma - murjantyo, cita herawati (Indonesian Journal of Cancer, 2010)
NASOPHARYNGEAL CARCINOMA 1. INTRODUCTION :2. INDONESIA :    NPC-ENT 1st    ALL OF CANCER - IVthEARLY STAGE => DIFFICULT !!- NO SPECIFIC SYMPTOM- PHYSICAL EXT. NOT  VISIBLE Full text : http://www.scribd.com/doc/43598782/Palliative-Treatment-In-Nasopharyngeal-Carcinoma